The Use of Simulation Methods in Enhancing the Speaking Skills of Hospitality Students at D3 Hospitality Program - Reni Rosianna Lumbangaol; Hetty Zaharani; Juliana Juliana (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study was motivated by the low speaking proficiency of hospitality students at UCM Campus, particularly in terms of fluency, confidence, mastery of hospitality vocabulary, pronunciation accuracy, and the ability to respond to situations in hotel service. Conventional speaking instruction has not yet fully equipped students to communicate effectively in real-world scenarios as required by the hospitality industry. This study aims to analyse the effectiveness of simulation methods in improving the speaking skills of hospitality students. This study employs a quantitative approach using a quasi-experimental method with a one-group pretest-post-test design. The research subjects were D3 degree students in the Hospitality program at UCM Campus. Data were collected through speaking tests, assessment rubrics, observations, and documentation. The assessment indicators include fluency, pronunciation, word choice, sentence structure, clarity of information, self-confidence, politeness, communicative responsiveness, and appropriateness to the hospitality context. The research results show that in the pretest phase, 40% of students were in the “below average” category and 60% were in the “average” category. After the simulation method was implemented, the post-test results showed an improvement, with 76% of students in the “good” category and 24% in the “very good” category. These findings indicate that the simulation method effectively enhances students’ speaking skills by providing realistic, contextual learning that aligns with actual hotel work situations. Through simulations, students become accustomed to practicing service communication, such as greeting guests, taking reservations, explaining facilities, handling complaints, and performing check-in and check-out procedures. The simulation method is recommended as a relevant speaking instruction strategy for students in the D3 Hospitality program.